4x-7-2(4x+1)=-2(3+2x)-3

Simple and best practice solution for 4x-7-2(4x+1)=-2(3+2x)-3 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 4x-7-2(4x+1)=-2(3+2x)-3 equation:


Simplifying
4x + -7 + -2(4x + 1) = -2(3 + 2x) + -3

Reorder the terms:
4x + -7 + -2(1 + 4x) = -2(3 + 2x) + -3
4x + -7 + (1 * -2 + 4x * -2) = -2(3 + 2x) + -3
4x + -7 + (-2 + -8x) = -2(3 + 2x) + -3

Reorder the terms:
-7 + -2 + 4x + -8x = -2(3 + 2x) + -3

Combine like terms: -7 + -2 = -9
-9 + 4x + -8x = -2(3 + 2x) + -3

Combine like terms: 4x + -8x = -4x
-9 + -4x = -2(3 + 2x) + -3
-9 + -4x = (3 * -2 + 2x * -2) + -3
-9 + -4x = (-6 + -4x) + -3

Reorder the terms:
-9 + -4x = -6 + -3 + -4x

Combine like terms: -6 + -3 = -9
-9 + -4x = -9 + -4x

Add '9' to each side of the equation.
-9 + 9 + -4x = -9 + 9 + -4x

Combine like terms: -9 + 9 = 0
0 + -4x = -9 + 9 + -4x
-4x = -9 + 9 + -4x

Combine like terms: -9 + 9 = 0
-4x = 0 + -4x
-4x = -4x

Add '4x' to each side of the equation.
-4x + 4x = -4x + 4x

Combine like terms: -4x + 4x = 0
0 = -4x + 4x

Combine like terms: -4x + 4x = 0
0 = 0

Solving
0 = 0

Couldn't find a variable to solve for.

This equation is an identity, all real numbers are solutions.

See similar equations:

| (2p-1)(p+1)=0 | | -4x-15=-31 | | 5-23=9x-5-8x | | -3(y-3y)+9=-2(4y-y)+1+11y | | 8+5x-1-3x=2x+3+3x+1-4x | | 3(x+8)-3x=-2(-4x+2) | | y(2/y) | | 15-6x=5-8x | | -3(x+6)+5=7(x+4)+1 | | 41/28=7/x | | 3a+9-a+8= | | 7(x-4)+8=3(x-4) | | 112-x=161 | | 12-2c=c | | 2x^2-4kx+3=0 | | 7x+7(-3x-11)=-161 | | -8-10=-1+7y | | -v+269=170 | | 0.9x-0.3(5-x)=3.9 | | 36x^3-4x=0 | | .50y+2.3=1.65 | | 10+9x=-22+x | | 83=-2x+5(-3x-14) | | 90=253-w | | x^4-7*2+12=0 | | -7+x+7x=41 | | 10+9x=-20+x | | x/6=-43 | | 41x=1974 | | -7-7(-4x-9)=168 | | 6z^2-7z+12=0 | | x+.06x=27120 |

Equations solver categories